Metastable precipitate phases in Mg–9.8 wt%Sn alloy. (1st February 2018) - Liu, C.Q.; Chen, H.W.; Liu, H.; Zhao, X.J.; Nie, J.F.
Abstract: Aberration-corrected scanning transmission electron microscopy has been used to characterize precipitates in a binary Mg–9.8 wt%Sn alloy aged in the temperature range 100–250 °C. In contrast to the traditional view that precipitation in Mg–Sn based alloys involves exclusive formation of the equilibrium phase β (Mg2 Sn, face-centered cubic), we found the formation of a GP zone and a metastable phase, designated β′, prior to the equilibrium β phase. The GP zone has a plate morphology with its habit plane parallel to the basal plane of the matrix phase. The β′ phase also has a plate morphology with its habit plane parallel to the magnesium basal plane. It has a L12 structure (space group P m 3 ¯ m, lattice parameter a  = 0.453 nm) and a Mg3 Sn composition. The orientation relationship between the β′ precipitate and the magnesium matrix is such that (11 1 ¯ )β′ // (0001)α and [011]β′ // [2 1 ¯ 1 ¯ 0]α . The β′ phase forms from GP zones and the magnesium matrix. Its formation is similar to the classical hcp → fcc transformation that involves generation and motion of Shockley partial dislocations on (0002)α . With prolonged ageing, some β′ precipitates transform in situ to the β phase. Graphical abstract: Image